BIAS JENDER DALAM NASKAH KHUTBAH JUM’AT - Arifinsyah, A. (UIN Sumatera Utara Medan, 2018)
In developing the da'wah, the main source of which is the Qur'an and the hadith and its interpretation, is certainly indispensable from place and time of interpretation in the sense that the scholars' understanding of religious texts is always related and influenced by historical, sociological, anthropological, and others in which the cleric lives. This study aims to find out the traditional interpretation that is often used by preachers as the material of preaching or Friday sermons, and to explore the root of the problem of gender bias in these texts, and to clarify the extent to which interpretations of religious texts relate to gender. This study used a qualitative approach to analyze the available literature. The object of the Friday sermon text is focused on a published Friday sermon text relevant to gender issues. The problem How does the religious doctrine of gender be interpreted in the Friday sermon text ?. The authors of the Friday sermon script seem to limit women's alignment with men, especially in the context of social roles. His views are trapped in myths about female inferiority and male superiority. Thus, the authors' interpretation of women's position and role in Islam is still biased. In order to preach the sermon or sermon optimally delivered the message of Islam grace al-alamin, required a standard interpretation according to the demands of the times and contextual.